2017
DOI: 10.1016/j.molcel.2017.04.022
|View full text |Cite|
|
Sign up to set email alerts
|

RFWD3-Mediated Ubiquitination Promotes Timely Removal of Both RPA and RAD51 from DNA Damage Sites to Facilitate Homologous Recombination

Abstract: RFWD3 is a recently identified Fanconi anemia protein FANCW whose E3 ligase activity toward RPA is essential in homologous recombination (HR) repair. However, how RPA ubiquitination promotes HR remained unknown. Here, we identified RAD51, the central HR protein, as another target of RFWD3. We show that RFWD3 polyubiquitinates both RPA and RAD51 in vitro and in vivo. Phosphorylation by ATR and ATM kinases is required for this activity in vivo. RFWD3 inhibits persistent mitomycin C (MMC)-induced RAD51 and RPA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
144
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 54 publications
5
144
0
1
Order By: Relevance
“…Importantly, FANCM-FAAP24 was also found to interact with ATR-ATRIP and HCLK2 in FA -A, C, and G cells [69], this observation is distinct from the role of FANCM in forming the FA complex E3, which activates FANCD2/I [12]. Aside from FANCM affecting ATR activation, the newly identified FANCW also plays an important role in ATR functions, at which point can ubiquitinate RPA and modulate the functions of RPA [4, 5]. In addition, the relationship between the FA proteins and ATR may be mutual and of equally importance.…”
Section: Fa Signaling and Master Regulators Of Cellular Stress Rementioning
confidence: 99%
“…Importantly, FANCM-FAAP24 was also found to interact with ATR-ATRIP and HCLK2 in FA -A, C, and G cells [69], this observation is distinct from the role of FANCM in forming the FA complex E3, which activates FANCD2/I [12]. Aside from FANCM affecting ATR activation, the newly identified FANCW also plays an important role in ATR functions, at which point can ubiquitinate RPA and modulate the functions of RPA [4, 5]. In addition, the relationship between the FA proteins and ATR may be mutual and of equally importance.…”
Section: Fa Signaling and Master Regulators Of Cellular Stress Rementioning
confidence: 99%
“…RFWD3 (RING finger and WD repeat domain‐containing protein 3) is a WDR‐containing E3 originally identified as an ATM/ATR substrate involved in DDR . Evidence has shown that the WDR domain is primarily responsible for the functional interactions that allow RFWD3 to maintain genomic stability . Furthermore, heritable mutations, particularly an Ile639Lys point mutation within the WDR domain, may lead to the rare genomic instability disease known as Fanconi anemia (FA), thereby implicating RFWD3 as a potential FA‐associated gene (alias: FANCW ) .…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Evidence has shown that the WDR domain is primarily responsible for the functional interactions that allow RFWD3 to maintain genomic stability. 4,5 Furthermore, heritable mutations, particularly an Ile639Lys point mutation within the WDR domain, may lead to the rare genomic instability disease known as Fanconi anemia (FA), 6 thereby implicating RFWD3 as a potential FA-associated gene (alias: FANCW). [4][5][6] Until recently, the biochemical characterization of RFWD3 has lacked complementary highresolution structural information.…”
mentioning
confidence: 99%
“…Furthermore, the VCP/p97-mediated extraction is now established as an integral part in fundamental chromatin-related processes (15), such as DNA replication (16), DNA damage response (17), double-strand break repair (18,19), DNA cross-link repair (20) and nucleotide excision repair (21,22). These VCP/p97 functions provide a rational understanding of the diverse phenotypic feathers (Figure 1), as described by Skrott et al (11), when NPL4 function is impaired or poisoned by DSF’s metabolite, DTC-copper complex [bis (diethyldithiocarbamate)–copper (CuET)].…”
mentioning
confidence: 99%
“…Since the VCP/p97 segregase complex is involved in a variety of cellular functions, the findings may open a wide window to gain better insight into how DSF may be used in clinical trials or translational studies in future (Figure 1). For example, tests of DSF as radio-sensitizer can be based on the role of VCP/p97-UFD1-NPL4 in double-strand break repair (1719). Similarly, trials of combinational use of DSF with DNA-damage therapeutics such as platinum and Et-743 can be rationalized by the role of VCP/p97-UFD1-NPL4 in nucleotide excision repair (21,22) and DNA cross-link repair (20).…”
mentioning
confidence: 99%